Antiglare antireflection plate
Patent Information
- Application Number
- JP2024134840
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-14
- Filing Date
- 2024-08-13
- Publication Date
- 2025-02-27
AI Technical Summary
【0008】 本発明の防眩性反射防止板は、高度の反射防止能に加えて防眩性に優れる。従って、一般の表示装置のみならず、自動者のメーターパネルやカーナビゲーションシステムのタッチパネルなどの高い視認性が要求される装置のパネルに有効に使用される。更にはスマートフォン、タブレット等の屋外で使用される表示装置にも好適に使用できる。 上記防眩性反射防止板をコーティング法で作製できるので、防眩性のバラツキが抑制される、基材の大きさに左右されず任意の防眩性反射防止板を作製できる、生産性およびコストの点で有利であるなどの顕著な工業的価値を有する。
Smart Images

Figure 2025027461000007 
Figure 2025027461000008 
Figure 2025027461000009
Abstract
Description
[Technical field]
[0001] The present invention relates to an antiglare and antireflection plate having excellent antireflection and antiglare properties. [Background technology]
[0002] Conventionally, in various display devices such as personal computers, mobile phones, liquid crystal monitors, automated teller machines, and automobile meter panels and navigation panels, it has been an issue to prevent reflections and glare under natural and artificial light in order to avoid a decrease in visibility, and various countermeasures have been implemented. As a countermeasure, anti-reflective film (plate) was developed, and the purpose is achieved by attaching this film to the surface of the display device. The anti-reflective film has an anti-reflective film made of an interference layer on the surface, which reduces the reflectance on the surface, prevents glare, etc., and ensures good visibility.
[0003] Another optical property that affects visibility is glare caused by the diffuse reflection or diffusion of light on the surface. To suppress glare (hereinafter referred to as anti-glare), technology has been developed to impart irregularities to the surface in order to disperse and diffuse light. Conventionally, methods for imparting unevenness to a surface have been adopted, such as embossing by hot pressing using a mold with unevenness processing, or uneven shaping by an embossing roller (Patent Documents 1 and 2). However, such physical shaping methods have the following problems. - Anti-glare properties vary because embossing cannot be done uniformly - Anti-glare properties vary depending on the type of substrate The embossing range is limited by the size of the embossing machine and the size of the substrate. -Since there is a difference in anti-glare properties between the center and edges of the substrate, the edges must be cut off, reducing the effective usable area and reducing productivity. -Increased production process and batch processing lead to poor production efficiency and increased costs [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-77279 A [Patent Document 2] JP 2004-333936 A Summary of the Invention [Problem to be solved by the invention]
[0005] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems and have discovered that by providing an antiglare layer on the surface layer of an antireflection plate and producing this antiglare layer by a coating method in which a curable composition containing particles of a specific particle size is applied and cured, it is possible to control the line roughness characteristics of the surface and thereby achieve antiglare properties, thereby completing the present invention. [Means for solving the problem]
[0006] That is, according to the present invention, there is provided an anti-glare and anti-reflection plate comprising a hard coat layer, an anti-glare layer, and an anti-reflection film laminated in this order on a transparent resin substrate, the anti-glare layer being made of a cured product of a composition containing 0.1 to 15.0 parts by mass of inorganic particles having an average particle diameter (D50) of 500 nm to 700 nm per 100 parts by mass of a polymerizable acrylate compound, and the surface of the anti-glare and anti-reflection plate has the following line roughness characteristic defined in JIS B 0601: Arithmetic mean roughness (Ra) is 0.03μm or more and 0.20μm or less. The average length (RSm) is 10 μm or more and 70 μm or less. Skewness (Rsk) is between -0.05 and 1.50. Kurtosis (Rku) is 2.0 or more and 5.0 or less; Maximum peak height (Rp) / maximum valley depth (Rv) is 1.0 or more and 3.0 or less The antiglare antireflection plate is characterized in that
[0007] In the above anti-glare anti-reflection plate invention, 1) The anti-reflection film is composed of a low refractive index layer having a refractive index of 1.20 to 1.45 and a layer thickness of 50 to 200 nm, the inorganic particles are silica particles, and the haze value of the anti-glare anti-reflection plate is 0.5 to 20.0%; 2) the anti-reflection film comprises a medium refractive index layer having a refractive index of 1.50 to 1.75 and a layer thickness of 50 to 200 nm, a high refractive index layer having a refractive index of 1.60 to 2.00 and a layer thickness of 50 to 200 nm, and a low refractive index layer having a refractive index of 1.20 to 1.45 and a layer thickness of 50 to 200 nm, in this order; the refractive index of the high refractive index layer is higher than that of the medium refractive index layer; the inorganic particles are silica particles; and the haze value of the anti-glare anti-reflection plate is 0.5 to 15.0%; 3) the antiglare layer is made of a cured product of a composition containing 100 parts by mass of a polymerizable acrylate compound consisting of 70 to 90% by mass of a hexafunctional urethane (meth)acrylate compound and 30 to 10% by mass of a di- to tetrafunctional (meth)acrylate compound (total 100% by mass), 0.1 to 15.0 parts by mass of inorganic particles, 0.1 to 1.0 part by mass of a metal chelate compound, and 0.0 to 45.0 parts by mass of silica fine particles; 4) The average thickness of the antiglare layer is 100 to 500 nm. 5) A protective layer and an antifouling layer are laminated in this order above the antireflection film (on the viewing side); is preferred. Effect of the Invention
[0008] The antiglare antireflection plate of the present invention has excellent antiglare properties in addition to high antireflection properties. Therefore, it can be effectively used not only for general display devices but also for panels of devices that require high visibility, such as meter panels for automobiles and touch panels for car navigation systems. It can also be suitably used for display devices used outdoors, such as smartphones and tablets. Since the antiglare antireflection plate can be produced by a coating method, it has significant industrial value, for example, in that variations in antiglare properties are suppressed, any antiglare antireflection plate can be produced regardless of the size of the substrate, and it is advantageous in terms of productivity and cost. [Brief description of the drawings]
[0009] [Figure 1] 1 is a laser photograph of the surface of the antiglare antireflection plate obtained in Example 1. [Diagram 2] FIG. 2 is a measurement cross-sectional curve diagram and a roughness curve diagram of the anti-glare and anti-reflection plate obtained in Example 1. [Diagram 3] 2 is a laser photograph of the surface of the antiglare antireflection plate obtained in Comparative Example 1. [Figure 4] FIG. 2 is a measurement cross-sectional curve diagram and a roughness curve diagram of the anti-glare anti-reflection plate obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Anti-glare anti-reflection plate> The antiglare and antireflection plate of the present invention has a basic structure in which a transparent resin substrate, a hard coat layer, an antiglare layer, and an antireflection film are laminated in this order. The anti-glare anti-reflection plate of the present invention is not limited in structure as long as it has the above-mentioned basic structure. For example, it is a preferred embodiment to provide a protective layer on the anti-reflection film (on the viewing side) that imparts abrasion resistance, and further provide an anti-fouling layer on the protective layer that prevents contamination by oily components or chemicals. In addition, a pressure-sensitive adhesive layer made of an acrylic, rubber, or silicone pressure-sensitive adhesive can be provided on the back side of the anti-glare anti-reflection plate. Furthermore, a hard coat layer, an anti-glare layer, and an anti-reflection film may be laminated on both the front and back sides of the transparent resin substrate. The antiglare and antireflection plate has the following surface characteristics (line roughness characteristics defined in JIS B 0601) and has excellent antiglare properties. Arithmetic mean roughness (Ra) is 0.03μm or more and 0.20μm or less, Average length (RSm) is 10 μm or more and 70 μm or less, Skewness (Rsk) is between -0.05 and 1.50, Kurtosis (Rku) is 2.0 or more and 5.0 or less, Maximum peak height (Rp) / maximum valley depth (Rv) is 1.0 or more and 3.0 or less.
[0011] [Arithmetic mean roughness (Ra)] The arithmetic mean roughness (Ra) represents the average of R(x) <absolute value> over a reference length. The arithmetic mean roughness (Ra) is 0.03 μm or more and 0.20 μm or less.
[0012] [Average length (RSm)] The average length (RSm) represents the average length of the contour curve element in the reference length, and Xsi is the length corresponding to one contour curve element. In this case, the peaks (valleys) that make up the contour element have minimum heights and lengths, and any peaks (valleys) whose height (depth) is 10% or less of the maximum height, or whose length is 1% or less of the length of the calculation section, are considered noise and are recognized as part of the valleys (peaks) that follow before and after. The average length (RSm) is between 10 μm and 70 μm, which suggests that not only the unevenness caused by the inorganic particles contained in the sample, but also the unevenness caused by the curable polymerizable acrylate compound, also contribute to the unevenness.
[0013] [Skewness (Rsk)] Skewness (Rsk) represents the cube mean of R(x) over a reference length, which has been made dimensionless by the cube of the root mean square height (Rq), and is a parameter that is closely related to tribology (friction). It expresses the degree of distortion and measures the symmetry of the distribution of peaks and valleys. If it is a normal distribution, it is 0 (zero), but if it is a worn surface, it is a negative value, indicating that the distribution is biased upward. The relevant skewness (Rsk) is between -0.05 and 1.50, indicating that there are many relatively fine peaks.
[0014] [Kurtosis (Rku)] Kurtosis (Rku) represents the fourth-mean square of R(x) over a reference length, non-dimensionalized by the fourth power of the root-mean-square height (Rq), and is a parameter closely related to tribology (friction). This indicates the degree of sharpness, and if it were a normal distribution, it would be 3. The kurtosis (Rku) is between 2.0 and 5.0, which indicates that the surface is not very sharp, but the surface is rough overall.
[0015] [Maximum peak height (Rp) / Maximum valley depth (Rv)] This indicates how many times the height of a peak is compared to the depth of a valley, and the larger the value, the higher the peak and the shallower the valley. The maximum peak height (Rp) / maximum valley depth (Rv) is between 1.0 and 3.0, which indicates that the height of the peak is relatively greater than the depth of the valley.
[0016] [Haze value] The antiglare antireflection plate of the present invention satisfies the above-mentioned surface characteristics, and as a result, has a haze value of 0.5 to 20.0%, and is excellent in antiglare properties. The haze value is affected by the layer structure of the antireflection film, but falls within the range, suppressing glare. The haze value is a physical value that is a scale of antiglare properties. The higher the haze value, the higher the antiglare properties. However, if the haze value exceeds 20.0%, the transparency of the antiglare antireflection plate decreases, which is not preferable. If the haze value is less than 0.5%, the transparency is high, but the glare is large, which reduces visibility. The preferred haze value is 0.5 to 15.0%, and the more preferred haze value is 0.8 to 13.5%.
[0017] <Transparent resin base material> The resin substrate is preferably one having light-transmitting properties in view of its intended use, and is preferably, for example, a substrate made of a thermoplastic resin having a total light transmittance of 85% or more at a wavelength of 750 to 400 nm. The thickness of the substrate is selected arbitrarily depending on the intended use, but is usually 0.5 to 3 mm. Examples of such a light-transmitting thermoplastic resin include acrylic resins such as polymethyl methacrylate, polycarbonate resins, polyethylene terephthalate resins, polyallyl diglycol carbonate resins, and polystyrene resins. The substrate may be a laminated resin substrate in which two kinds of the above resins are laminated, but it is preferable that the surface on which the hard coat layer is formed is formed of an acrylic resin, a polycarbonate resin, or a polyethylene terephthalate resin. A laminated resin substrate of a polycarbonate resin and an acrylic resin is preferably used. Furthermore, such a transparent resin substrate may be colored with an oil-soluble dye or the like, so long as the light transmittance is not impaired.
[0018] <Hard coat layer> A hard coat layer is laminated on a transparent resin substrate, and an antiglare layer, which will be described later, is formed on this hard coat layer. The hard coat layer contributes to the strength of the antiglare antireflection plate and the adhesion between the transparent resin substrate and the antiglare layer. The improved adhesion leads to excellent abrasion resistance and hardness of the antiglare antireflection plate of the present invention. The thickness of the hard coat layer is usually 1 to 5 μm. If it is less than 1 μm, the properties such as strength of the hard coat layer are impaired, and if it exceeds 5 μm, cracks tend to occur. The thickness is preferably 1 to 3 μm, and particularly preferably 1 to 2 μm. In order to obtain excellent adhesion between the transparent resin substrate and the antiglare layer, as well as excellent hardness of the antiglare layer itself, a hard coat layer made of a cured product of a curable composition containing a polymerizable acrylate compound containing 70 to 90 mass % of a urethane (meth)acrylate compound having 6 or more functionalities, silica fine particles, a silane coupling agent, and a metal chelate compound is suitable. A typical formulation of the curable composition is 100 parts by mass of a polymerizable acrylate compound consisting of 80 to 90% by mass of a urethane (meth)acrylate compound having 6 or more functionalities and 20 to 10% by mass of a (meth)acrylate compound (total 100% by mass), 20 to 50 parts by mass of silica fine particles, 5 to 15 parts by mass of a silane coupling agent, and 0.1 to 1.5 parts by mass of a metal chelate compound.
[0019] [Six or more functional urethane (meth)acrylate compounds; hereinafter, also referred to as hexafunctional urethane (meth)acrylates] Hexafunctional urethane (meth)acrylate is a polymerizable acrylate compound obtained by addition reaction of a terminal isocyanate compound obtained by reacting a polyol compound with a diisocyanate compound with a (meth)acrylate compound having multiple hydroxyl groups, and can be obtained by reacting these two raw materials in a molar ratio that provides 6 or more times the amount of (meth)acryloyl groups and reacting them by a method known per se. For example, a hexafunctional urethane (meth)acrylate having three (meth)acryloyl groups at each molecular chain end can be obtained by reacting pentaerythritol tri(meth)acrylate with a terminal isocyanate (e.g., trihexadiethylene diisocyanate). Specific examples of the hexafunctional urethane (meth)acrylate include dipentaerythritol hexa(meth)acrylate, phenyl glycidyl ether (meth)acrylate hexamethylene diisocyanate urethane prepolymer, phenyl glycidyl ether (meth)acrylate isophorone diisocyanate urethane prepolymer, phenyl glycidyl ether (meth)acrylate tolylene diisocyanate urethane prepolymer; glycerin di(meth)acrylate tolylene diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate hexamethylene diisocyanate urethane oligomer, glycerin di(meth)acrylate isophorone diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate tolylene diisocyanate urethane oligomer, pentaerythritol tri(meth)acrylate isophorone diisocyanate urethane preoligomer, and the like. These may be used alone or in combination of two or more. These hexafunctional urethane (meth)acrylates are commercially available, for example, as the Art Resin series (Negami Chemical Industry Co., Ltd.), the U / UA Oligo series (Shin-Nakamura Chemical Co., Ltd.), the Shikoh UV series (Nippon Synthetic Chemical Industry Co., Ltd.), and the Urethane Acrylate UA series (Kyoeisha Chemical Co., Ltd.), and are generally available. If the blending ratio of the hexafunctional urethane (meth)acrylate in the polymerizable acrylate compound is less than 70% by mass, the abrasion resistance tends to be poor, which is not preferable. If it exceeds 90% by mass, cracks tend to occur easily. Taking into consideration the hardness and impact resistance of the cured body, adhesion to the antiglare layer, and further coatability, it is preferable to use it by mixing it with other polymerizable acrylate compounds described below.
[0020] [Other polymerizable acrylate compounds] Other polymerizable acrylate compounds include monofunctional (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, lauryl (meth)acrylate, and hydroxyethyl (meth)acrylate; bifunctional (meth)acrylate compounds such as ethylene glycol di(meth)acrylate and triethylene glycol di(meth)acrylate; and tri- to tetrafunctional (meth)acrylate compounds such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and trimethylolpropane tri(meth)acrylate. Further examples include di- to tetrafunctional urethane (meth)acrylate compounds obtained by polyaddition reaction of a diisocyanate compound with a (meth)acrylate compound having multiple hydroxyl groups, and in which the number of (meth)acryloyl groups is controlled to 2 to 4. These other polymerizable acrylate compounds are commercially available and therefore generally available, and may be used alone or in combination depending on the purpose.
[0021] [Silica fine particles] The silica fine particles used in the hard coat layer are particles that contribute to improving adhesion and coatability, and their properties are not particularly limited. Usually, spherical particles with an average particle diameter (D50) of 5 to 50 nm and a refractive index of 1.44 to 1.50 are used. If the average particle diameter (D50) is out of this range, the coatability tends to deteriorate. The average particle diameter of the particles used in the present invention means the particle diameter (D50) at 50% cumulative value in the particle size distribution obtained by the laser diffraction / scattering method. The silica microparticles are single-particle, dense, non-hollow particles with no internal cavities, and have a density of typically 1.9 g / cm 3 That is all. The silica fine particles are known per se and are commercially available. Commercially available silica fine particles are usually provided in a state of being dispersed in a solvent, and therefore the solvent is inevitably mixed into the solution (coating liquid) of the curable composition for forming the hard coat layer, and behaves in the same manner as other solvents.
[0022] [Silane coupling agent] Silane coupling agent is hydrolyzed by itself to form dense siliceous coating. Known ones can be used without limitation, and specific examples include γ-(meth)acryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-anilinopropyltrimethoxysilane, γ-(N-styrylmethyl-β-aminoethylamino)propyltrimethoxysilane hydrochloride, γ-mercaptopropyltrimethoxysilane, etc. For the purpose of improving the solubility in water or a solvent, the silane coupling agent is preferably hydrolyzed in advance with a dilute acid or the like, depending on the type, and includes the hydrolyzate. There is no particular restriction on the method of pre-hydrolysis, and a method of partially hydrolyzing the silane coupling agent using an acid catalyst such as acetic acid is generally used.
[0023] [Metal chelate compounds] The metal chelate compound functions to introduce a crosslinked structure into the hard coat layer, thereby making it more dense. As described above, the hard coat layer of the present invention uses a large amount of hexafunctional urethane (meth)acrylate, and therefore has high flexibility but low density. The metal chelate compound is used to compensate for the low density without impairing flexibility. In addition, since such a metal chelate compound is also contained in the antiglare layer, the adhesion between the hard coat layer and the antiglare layer is further improved.
[0024] The metal chelate compound is a compound in which a chelating agent, typically a bidentate ligand, is coordinated to a metal such as titanium, zirconium, or aluminum, and any known compound can be used without limitation. Aluminum chelate compounds are preferred, and specific examples thereof include diethoxy mono(acetylacetonate)aluminum, monoethoxy bis(acetylacetonate)aluminum, di-i-propoxy mono(acetylacetonate)aluminum, monoethoxy bis(ethylacetoacetate)aluminum, diethoxy mono(ethylacetoacetate)aluminum, and aluminum triacetylacetonate.
[0025] [Formation of hard coat layer] The above essential components and optional components are usually mixed and stirred in any order with the organic solvent described below at about room temperature to form a solution (coating liquid) of the curable composition. This solution is applied to the transparent resin substrate, dried at 50° C. or higher to remove the solvent, and then cured by irradiating with ultraviolet light to form a hard coat layer. As optional components, a polymerization initiator for curing the curable composition, a hydrolysis catalyst for promoting condensation curing, an ultraviolet absorber, an organic solvent for dilution to prepare a coating liquid, and the like are used. As the polymerization initiator, a known thermal polymerization initiator or photopolymerization initiator is used in a catalytic amount.As the hydrolysis catalyst, an aqueous solution of an acid such as hydrochloric acid, sulfuric acid, nitric acid, or acetic acid is used in a catalytic amount. From the viewpoint of coatability, the organic solvent is usually used so that the total concentration of essential and optional components is 15 to 40 mass%. Suitable organic solvents to be used include alcohol-based solvents such as ethyl alcohol and (iso)propyl alcohol; aromatic solvents such as toluene and xylene; acetate-based solvents such as (iso)butyl acetate; and ketone-based solvents such as methyl ethyl ketone and methyl isobutyl ketone. These organic solvents are evaporated and removed when the hard coat layer is formed. The method for applying the coating liquid onto the transparent resin substrate is not particularly limited, and methods such as dip coating, roll coating, die coating, flow coating, and spraying can be used. From the viewpoints of appearance quality and layer thickness control, the dip coating method is preferred.
[0026] <Anti-glare layer> An antiglare layer is provided on the hard coat layer. In the present invention, the antiglare layer is formed by a coating method and is characterized in that it is made of a cured product of a composition containing 0.1 to 15.0 parts by mass of inorganic particles having an average particle size (D50) of 500 nm to 700 nm per 100 parts by mass of a polymerizable acrylate compound. The thickness of the antiglare layer is usually 100 to 500 nm. If it is less than 100 nm, the inorganic particles tend to protrude too much. If an antireflection film is laminated on the antiglare layer, the protruding inorganic particles will enter the antireflection film and increase the refractive index. As a result, the reflectance increases and the antireflection ability is impaired. If it exceeds 500 nm, the inorganic particles will be buried in the binder component more and the antiglare properties will not be fully expressed. In addition, the transparency of the antiglare antireflection plate will decrease, which is not preferable. It is preferably 150 to 450 nm, and particularly preferably 200 to 400 nm. A suitable formulation of the curable composition is 100 parts by mass of a polymerizable acrylate compound consisting of 70 to 90% by mass of a hexafunctional urethane (meth)acrylate and 30 to 10% by mass of a di- to tetrafunctional (meth)acrylate compound (total 100% by mass), 0.1 to 15.0 parts by mass of inorganic particles, 0.1 to 1.0 part by mass of a metal chelate compound, and 0.0 to 45.0 parts by mass of silica fine particles. The surface characteristics of the formed antiglare layer are followed and maintained even if an antireflection film, a protective layer, or an antifouling layer is provided on the antiglare layer, and as a result, the antiglare antireflection plate exhibits the above-mentioned surface characteristics (line roughness characteristics) and exhibits antiglare properties.
[0027] [Polymerizable acrylate compound] The polymerizable acrylate compound is a general term for acrylate-based polymerizable compounds including the above-mentioned hexafunctional urethane (meth)acrylate and other polymerizable acrylate compounds. From the viewpoint of adhesion between the hard coat layer and the antireflection layer, the polymerizable acrylate compound in the curable composition for forming the antiglare layer is preferably a mixed composition of 70 to 90 mass % of a hexafunctional urethane (meth)acrylate and 30 to 10 mass % of a di- to tetrafunctional (meth)acrylate compound.
[0028] [Inorganic particles] In order for the antiglare antireflection plate of the present invention to exhibit the above-mentioned line roughness characteristics, it is necessary to use inorganic particles having an average particle size (D50) of 500 nm to 700 nm. When inorganic particles having an average particle diameter (D50) within the above range are used, the antiglare antireflection plate of the present invention exhibits the above-mentioned surface characteristics (line roughness characteristics) due to the size, thereby exhibiting antiglare properties. If the particle diameter is less than 500 nm, the antiglare properties are not exhibited, and if the particle diameter exceeds 700 nm, white blur (white turbidity) occurs, causing poor appearance. Since the surface characteristics depend on the average particle size (D50) of the particles used, there are no particular limitations on the chemical composition or characteristics of the particles, so long as the particles have an average particle size (D50) within the above range, as long as they do not chemically deteriorate the antiglare layer or antireflection film.Specific examples of the particles include inorganic oxide particles such as silica, alumina, zirconia, titania, and zinc oxide; nitride particles such as aluminum nitride and boron nitride; and inorganic salt particles such as magnesium sulfate and calcium carbonate. The inorganic particles must be blended in the range of 0.1 to 15.0 parts by mass per 100 parts by mass of the polymerizable acrylate compound. If the amount is less than 0.1 part by mass, the above-mentioned surface characteristics (line roughness characteristics) are not expressed. If the amount exceeds 15.0 parts by mass, white blur occurs, which is not preferable.
[0029] [Silica particles] Among inorganic particles, silica particles are particularly suitable in terms of not causing chemical deterioration of the antiglare layer or antireflection film and being easily available. Silica particles have the same chemical composition and structure as the silica fine particles used in the hard coat layer described above, but are significantly different in that their average particle diameter (D50) is 500 nm to 700 nm. Silica particles are known per se and are usually commercially available in a state dispersed in a solvent. In addition, the silica fine particles described above may be blended in order to improve coating properties.
[0030] [Formation of antiglare layer] The above essential components and further optional components are usually mixed and stirred in any order with the following organic solvent at around room temperature to form a solution (coating liquid) of the curable composition. After this solution is applied onto the hard coat layer, it is dried at 50° C. or higher to remove the solvent, and then cured by irradiation with ultraviolet light to form an antiglare layer. Optional components include metal chelate compounds, polymerization initiators, silica fine particles, etc. These optional components, organic solvents for dilution, coating methods, etc. are the same as those for the hard coat layer.
[0031] <Anti-reflective film> The antiglare antireflection plate of the present invention comprises an antireflection film laminated on the antiglare layer. The antireflection film has a low refractive index layer having a refractive index of 1.20 to 1.45 as an essential layer. If the refractive index of the low refractive index layer is outside this range, it will not function as an antireflection film. In order to achieve high antireflection performance, it is preferable to use an antireflection film having a two-layer structure including a low refractive index layer having a refractive index of 1.20 to 1.45 and a high refractive index layer having a refractive index of 1.60 to 2.00. A more preferable embodiment is to use an antireflection film having a three-layer structure in which a medium refractive index layer having a refractive index of 1.50 to 1.75 and lower than the high refractive index layer is provided below (on the antiglare layer side) the high refractive index layer. When the antireflection film is made up of a plurality of refractive index layers, the low refractive index layer is located on the outermost layer (viewing side) of the antireflection film.
[0032] [Low Refractive Index Layer] The low refractive index layer is typically formed by curing a curable composition containing a silane coupling agent, a metal chelate compound, and hollow silica fine particles. The hollow silica fine particles are mixed in an amount of 30 to 200 parts by mass per 100 parts by mass of the silane coupling agent. If the amount is less than 30 parts by mass, a low refractive index cannot be achieved, and if the amount exceeds 200 parts by mass, the abrasion resistance decreases. In addition to the above essential components, the curable composition for forming the low refractive index layer may contain an appropriate amount of an acid aqueous solution such as an aqueous hydrochloric acid solution in order to promote hydrolysis and condensation of the silane coupling agent.
[0033] [Hollow Silica Microparticles] The hollow silica fine particles contained in the low refractive index layer are particles that control the refractive index of the layer. The average particle diameter (D50) is usually 10 to 150 nm, preferably 50 to 100 nm, and more preferably 50 to 70 nm. The hollow silica fine particles are hollow inside, with a porosity of 20 to 70%, preferably 30 to 50%, and a refractive index of usually 1.30 or less. The hollow silica fine particles are commercially available in a state dispersed in a solvent, and may be appropriately selected and procured for use.
[0034] [Formation of low refractive index layer] The low refractive index layer is formed in the same manner as in the formation of the hard coat layer, by applying a curable composition solution (coating liquid) for forming the low refractive index layer onto the antiglare layer, drying it, and then heating and curing it at 70 to 120° C. The thickness of the layer is usually set in the range of 50 to 200 nm from the viewpoint of antireflection performance. When the antireflection film is composed of two layers, a high refractive index layer and a low refractive index layer, the high refractive index layer is first formed on the antiglare layer, and then the low refractive index layer is formed on the high refractive index layer.When the antireflection layer is composed of three layers, a medium refractive index layer, a high refractive index layer, and a low refractive index layer, the medium refractive index layer is first formed on the antiglare layer, and then the high refractive index layer is formed on the high refractive index layer, and then the low refractive index layer is formed on the medium refractive index layer. The silane coupling agent, metal chelate compound, acid aqueous solution and organic solvent used in the coating liquid are the same as those described in the section on the hard coat layer. The coating method is also similar to that of the hard coat layer.
[0035] [Medium refractive index layer / High refractive index layer] In order to further enhance the antireflection ability, the antiglare antireflection plate of the present invention preferably has an antireflection film having a high-order structure including a high refractive index layer and further an intermediate refractive index layer. The medium refractive index layer preferably has a refractive index of 1.50 to 1.75 and a thickness of 50 to 200 nm. The high refractive index layer preferably has a refractive index of 1.60 to 2.00 and a thickness of 50 to 200 nm. In the antireflection film, it is essential that the refractive index of the high refractive index layer is higher than that of the medium refractive index layer. The high refractive index layer and the medium refractive index layer are typically formed by curing a curable composition containing 100 to 500 parts by mass of metal oxide particles per 100 parts by mass of a silane coupling agent. The amount of the metal oxide particles is appropriately determined depending on the metal oxide used and the refractive index to be set. The curable compositions for forming the high and medium refractive index layers may contain an appropriate amount of an aqueous acid solution, similar to the low refractive index layer.
[0036] [Metal oxide particles] The metal oxide particles are used for the purpose of adjusting the refractive index of the medium refractive index layer and the high refractive index layer to fall within the above-mentioned predetermined range. Typically, the metal oxide particles have an average particle size of 10 to 100 nm and a refractive index of 1.70 to 2.80. Specifically, zirconium oxide particles (refractive index = 2.40); composite zirconium metal oxide particles in which zirconium oxide and other oxides such as silicon oxide are combined at the molecular level to adjust the refractive index; titanium oxide particles (refractive index = 2.71); composite titanium metal oxide particles in which titanium oxide and other oxides such as silicon oxide and zirconium oxide are combined at the molecular level to adjust the refractive index, etc. are used. These metal oxide particles are selected or appropriately combined to adjust the layer to a desired refractive index. Such particles are known per se and are commercially available in a state of being dispersed in a solvent.
[0037] [Organic-inorganic composite compound] The medium refractive index layer and the high refractive index layer may contain an organic-inorganic hybrid compound for the purpose of improving the adhesion between the antiglare layer and the low refractive index layer. The organic-inorganic composite compound is, for example, a composite compound in which an alkoxysilyl group is bonded, which is obtained by reacting a hydrolyzable alkoxysilane compound with a bisphenol A type epoxy resin having an epoxy equivalent of 180 to 5000. When this composite compound is cured, crosslinking of the terminal epoxy group and high-order siloxane crosslinking (silica generation) due to the sol-gel reaction of the alkoxysilyl group occur, resulting in a cured product that has no Tg like glass and has the advantages of both organic and inorganic materials. There are various types of organic-inorganic hybrid compounds, including bisphenol A type epoxy resins (hereinafter also referred to as silane-modified epoxy compounds), novolac phenolic resins, and hybrid compounds having a structure in which alkoxysilyl groups are bonded to polymers such as polyamic acid compounds. In the present invention, as the organic-inorganic hybrid compound, a silane-modified epoxy compound is preferably used from the viewpoints of excellent adhesion between the antiglare layer and the refractive index layer and of ease of availability.
[0038] [Formation of medium refractive index layer and high refractive index layer] The medium refractive index layer and the high refractive index layer are formed in the same manner as the formation of the low refractive index layer, by applying each composition solution (coating liquid) onto the antiglare layer in the order described above, drying the composition solution, and then heating and curing the composition at 70 to 120°C. The silane coupling agent, metal chelate compound, acid aqueous solution and organic solvent used in each curable composition solution are the same as those described in the section on the hard coat layer. The coating method is also similar to that of the hard coat layer.
[0039] <Protective layer> In the present invention, a suitable protective layer is made of a cured product obtained by curing a curable composition containing 7.5 to 35 parts by mass of spherical silica fine particles having an average particle size of 10 nm or less, per 100 parts by mass in total of 90 to 98 parts by mass of a silane coupling agent and 10 to 2 parts by mass of a metal chelate compound. The refractive index of the cured product after curing is preferably 1.45 to 1.50, and the thickness of the layer is preferably 10 to 15 nm. The silane coupling agent, metal chelate compound and silica fine particles to be blended in the curable composition may be the same as those used in forming the hard coat layer, and the same is true for the coating method and the organic solvent for preparing the coating solution.
[0040] <Anti-stain layer> This layer is provided to exhibit high antifouling properties and is usually set to a thickness of 5 to 15 nm, and is made of a polymer of a fluorine-containing silicon compound. Specifically, the polymer of a fluorine-containing silicon compound is a polymer obtained by condensation polymerization of a compound having a perfluoropolyether structure as the main chain and an alkoxysilyl group, which is a hydrolyzable group, at one or both ends of the main chain. The presence of the perfluoropolyether structure reduces the adhesion of oil and fat, resulting in high antifouling properties. The fluorine-containing silicon compound is commercially available as a solution dissolved in an organic solvent such as isopropyl ether, hexane, or a fluorine-based organic solvent under the trade names of 3M (Novec®), Toray Dow Corning (Dow Corning®), Shin-Etsu Chemical (SHIN-ETSU SUBELYN®), Daikin (OPTOOL), and Asahi Glass (SURECO®), and it is preferable to obtain and use these. The solution (coating liquid) containing the above-mentioned fluorine-containing silicon compound is applied onto the protective layer by a conventional method, and then is kept at a temperature of about 100°C for about 6 to 8 hours, whereby the solution is dried and cured into a polymer, forming an antifouling layer. EXAMPLES
[0041] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Furthermore, not all of the combinations of features described in the examples are necessarily essential to the solution of the present invention. The various components, abbreviations and measurement methods used in the following Examples and Comparative Examples are as follows.
[0042] [Polymerizable acrylate compound] [Hexafunctional urethane (meth)acrylate] AC-6: Pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer [Bifunctional (meth)acrylate compounds] ac-2: Triethylene glycol diacrylate [Trifunctional (meth)acrylate compounds] ac-3: Polyester urethane acrylate ac-4: Pentaerythritol triacrylate [Silica fine particles] sp-1: solid sphere, average particle size (D50) = 7 nm, refractive index = 1.46, IPA dispersion, solid part: 20wt% sp-2: solid sphere, average particle size (D50) = 40 nm, refractive index = 1.46, MEK dispersion, solid part: 30wt% sp-3: hollow particles, average particle size (D50) = 60 nm, refractive index = 1.30, IPA dispersion, solid part: 20wt% [Silica particles] sp-4: solid sphere, average particle size (D50) = 500 nm, refractive index = 1.46, MEK dispersion, solid part: 67wt% sp-5: solid sphere, average particle size (D50) = 700 nm, refractive index = 1.46, MeOH dispersion, solid part: 50wt% sp-6: solid sphere, average particle size (D50) = 300 nm, refractive index = 1.46, MeOH dispersion, solid part: 33wt% sp-7: solid sphere, average particle size (D50) = 900 nm, refractive index = 1.46, MEK dispersion, solid part: 67wt% [Silane coupling agent] γ-GPS: γ-glycidoxypropyltrimethoxysilane [Metal chelate compounds] ATAA: Aluminum tris(acetylacetonate) [Metal oxide particles] z-1: zirconia particles, average particle size = 60 nm, refractive index = 2.42 PGM (1-methoxy-2-propanol) dispersion, solid content: 53wt% z-2: zirconia particles, average particle size = 30 nm, refractive index = 2.40, BuOH / EtOH dispersion, solid part: 15wt% [Organic-inorganic composite compound] sep: silane-modified epoxy compound, DMDG (Diethylene glycol dimethyl ether) dispersion [Photopolymerization initiator] pi-1: 1-Hydroxy-cyclohexyl-phenyl ketone pi-2: 2-methyl-1-[4-(methylthio)phenyl]-2- Morpholinopropan-1-one [Ultraviolet absorber] UV: Benzotriazole-based ultraviolet absorber [Hydrolysis catalyst] HCl: 0.05N hydrochloric acid aqueous solution [Organic solvent] IPA: Isopropyl alcohol MIBK: Methyl isobutyl ketone SBAC: secondary butyl ester of acetate NPA: Normal propyl alcohol Ethacol: A mixture of ethyl alcohol and isopropyl alcohol
[0043] [Luminous average reflectance] Using a JASCO Corporation "V-650" UV-Vis spectrophotometer, the reflectance at the lowest point (on the surface of the anti-glare anti-reflection plate) was measured at a scanning speed of 1000 nm / min and in the wavelength range of 380 to 780 nm. The reflectance was calculated by multiplying the obtained reflectance by the weighting coefficient described in JIS-Z-8722. The smaller the value, the better the anti-reflection performance.
[0044] [Luminous average transmittance] Using a JASCO Corporation "V-650" UV-Vis spectrophotometer, the transmittance at the peak top was measured in the range of 380 nm to 780 nm at a scanning speed of 1000 nm / min, and calculated by multiplying it by the weighting coefficient described in JIS-Z-8722.
[0045] [Various line roughness characteristics] Based on the Japanese Industrial Standard "JIS B 0601", measurements were taken using a Keyence "VK-X1000" laser microscope. The values of each line roughness characteristic were automatically calculated using the analysis software built into the measuring device. The measurement distance was 276 μm, and the first and last total of 26 μm was cut off.
[0046] [Maximum peak height (Rp) / Maximum valley depth (Rv)] This is a characteristic value uniquely set in the present invention, and is the maximum peak height (Rp) divided by the maximum valley depth (Rv) obtained using a Keyence Corporation "VK-X1000" laser microscope device.
[0047] [Haze value] Measured using a Murakami Color Research Laboratory "HM-150N" haze meter based on the Japanese Industrial Standard "JIS K 7136." If the haze value is less than 0.5%, glare will be observed on the surface, and if it is more than 20.0%, it will become cloudy and will not function as an anti-glare anti-reflection plate.
[0048] [Refractive Index] The coating solution for each refractive index layer was applied to an acrylic resin substrate to a thickness of 100 nm, and cured to form each refractive index layer. The refractive index of each layer was then calculated from the bottom value of the reflection spectrum using a JASCO V-650 spectrophotometer.
[0049] Example 1 A hard coat layer, an antiglare layer, and an antireflection film were formed on a transparent resin substrate made of polymethyl methacrylate resin (PMMA) with a thickness of 1 mm (80 mm length × 50 mm width) in the following manner. The thickness of each layer was adjusted by changing the withdrawal speed from the dipped coating liquid.
[0050] [Coating solution for forming hard coat layer; HC-1] Polymerizable acrylate compound: The compounding ratio per 100 parts by mass of the total amount of the compound is shown in parentheses (the same applies below). ·ac―6;126.7g (85.1 parts by mass) ·ac-2;8.0g (5.4 parts by mass) ·ac-3;14.1g (9.5 parts by mass) Silica Microparticles ·sp-1;40.0g (26.9 parts by mass), dispersion medium IPA160.0g Silane Coupling Agent ·γ-GPS; 12.2g (8.2 parts by mass) Metal Chelate Compounds ·ATAA;1.0g (0.7 parts by mass) UV absorbers UV: 11.2g Photoinitiator ·pi-1;6.4g pi-2; 1.6g Hydrolysis Catalyst HCl; 2.8 g Organic solvents IPA; 308.0g MIBK; 308.0g
[0051] [Anti-glare layer coating solution; AG-1] Polymerizable acrylate compounds: ·ac―6;25.2g (70.0 parts by mass) ·ac-4;10.8g (30.0 parts by mass) Silica Microparticles ·sp-2;4.0g (11.1 parts by mass), dispersion medium MEK9.3g Silica particles ·sp-4;0.2g (0.6 parts by mass), dispersion medium MEK0.1g Metal Chelate Compounds ·ATAA;0.2g (0.6 parts by mass) Photoinitiator ·pi-2;1.4g (3.9 parts by mass) Organic solvents IPA; 565.0g MIBK; 383.8g
[0052] [Low refractive index layer forming coating liquid; l-1]: The compounding ratio per 100 parts by mass of the silane coupling agent is shown in parentheses. Silane Coupling Agent ·γ-GPS; 3.6g (100 parts by mass) Silica Microparticles ·sp-3;1.7g (46.2 parts by mass), dispersion medium IPA6.7g Metal Chelate Compounds ·ATAA;0.1g (2.8 parts by mass) Hydrolysis Catalyst HCl; 1.7 g Organic solvents IPA; 147.7g NPA: 49.2g SBAC: 49.2g
[0053] First, a transparent resin substrate was dip-coated with the coating liquid for forming a hard coat layer having the above composition, dried at 60°C for 5 minutes, and then irradiated with ultraviolet light from a mercury lamp for 1 minute to be UV-cured, forming a hard coat layer having a thickness of 2 μm. Next, the substrate having the hard coat layer was dip-coated with the coating liquid for forming an antiglare layer, dried at 60°C for 8 minutes, and then irradiated with ultraviolet light from a mercury lamp for 1 minute to be UV-cured, forming an antiglare layer having a thickness of 200 nm. Then, the substrate having the hard coat layer and the antiglare layer was dip-coated with the coating liquid for forming a low refractive index layer, and then heat-treated at 90°C for 20 minutes to form an antireflection film (low refractive index layer) having a thickness of 95 nm and a refractive index of 1.34, thereby obtaining an antiglare antireflection plate of the present invention. The various physical properties and characteristics of the obtained antiglare antireflection plate were measured and evaluated according to the above-mentioned measuring methods. Table 2 shows the layer thickness and optical characteristics of each layer, and Table 3 shows the surface characteristics (various line roughness characteristics). Figure 1 shows a laser photograph of the surface, and Figure 2 shows the measured cross-sectional curve and roughness curve. From both figures, it can be seen that there are large protrusions.
[0054] Examples 2 to 3 An antiglare antireflection plate was produced and various physical properties and characteristics were measured in the same manner as in Example 1, except that the coating liquid for forming the antiglare layer was changed to a coating liquid having the blending composition shown in Table 1. The results are shown in Tables 2 and 3.
[0055] [Table 1]
[0056] Example 4 An antiglare antireflection plate was produced in the same manner as in Example 1, except that the antireflection film was a film having a three-layer structure of a medium refractive index layer, a high refractive index layer, and a low refractive index layer, and various physical properties and characteristics were measured. The results are shown in Tables 2 and 3. The antireflection film was prepared by first dip-coating a transparent resin substrate having a hard coat layer and an antiglare layer formed in this order with the following coating liquid for forming a medium refractive index layer, followed by heat treatment at 90°C for 20 minutes to form a medium refractive index layer (layer thickness 85 nm, refractive index 1.64), then dip-coating with the following coating liquid for forming a high refractive index layer, followed by heat treatment at 90°C for 20 minutes to form a high refractive index layer (layer thickness 80 nm, refractive index 1.77), and further forming a low refractive index layer as described in Example 1 in the same manner to obtain a three-layer antireflection film (film thickness 255 nm).
[0057] [Coating liquid for forming medium refractive index layer; m-1]: The compounding ratio per 100 parts by mass of the silane coupling agent is shown in parentheses. Silane Coupling Agent ·γ-GPS; 1.5g (100 parts by mass) Organic-inorganic composite compound ·sep;2.4g (160 parts by mass), dispersion medium DMDG2.4g metal oxide particles ·z-1;4.8g (320 parts by mass), dispersion medium PGM4.3g Metal Chelate Compounds ·ATAA;0.1g (6.7 parts by mass) Hydrolysis Catalyst HCl; 0.9 g Organic solvents IPA; 97.4g SBAC: 146.2g
[0058] [Coating liquid for forming high refractive index layer; h-1]: The compounding ratio per 100 parts by mass of the silane coupling agent is shown in parentheses. Silane Coupling Agent ·γ-GPS; 1.3g (100 parts by mass) metal oxide particles ·z-2;4.5g (346 parts by mass), dispersion medium BuOH / EtOH30.0g Metal Chelate Compounds ·ATAA;0.2g (15.4 parts by mass) Hydrolysis Catalyst HCl; 0.3 g Organic solvents SBAC: 11.2g Ethacol; 212.5g
[0059] Examples 5 to 7 An antiglare antireflection plate was produced in the same manner as in Example 4, except that the coating liquid for forming the antiglare layer was changed to a coating liquid having the composition shown in Table 1, and various physical properties and characteristics were measured. The results are shown in Tables 2 and 3.
[0060] [Table 2]
[0061] [Table 3]
[0062] Comparative Examples 1 to 6 Except for changing the coating liquid for forming the antiglare layer to a coating liquid having the blending composition shown in Table 4, an antiglare antireflection plate was produced and various physical properties and characteristics were measured in the same manner as in Examples 1 and 4. The results are shown in Tables 5 and 6.
[0063] [Table 4]
[0064] [Table 5]
[0065] [Table 6]
[0066] Comparative Example 1 is an example that does not contain inorganic particles with a large average particle size, and the haze value was small and the surface was clearly glare-prone. Figure 3 shows a laser photograph of the surface, and Figure 4 shows the measurement cross-sectional curve and roughness curve. Both figures show that there are no large protrusions. Comparative Example 2 is an example containing a large amount of inorganic particles with a large average particle size, and has a large haze value, is cloudy, and has no product value, so line roughness characteristics were not measured. In Comparative Example 3, the average particle size of the inorganic particles was too small, and the haze value was small and obvious glare was observed on the surface. In Comparative Example 4, the average particle size of the inorganic particles was too large, and the haze value was large and the product was cloudy and had no product value, so the line roughness characteristics were not measured. Comparative Example 5 is an example in which the antireflection film has a three-layer structure and does not contain inorganic particles with a large average particle size, and the haze value was small and glare was clearly observed on the surface. Comparative Example 6 is an example in which the anti-reflection film has a three-layer structure and contains a large amount of inorganic particles with a large average particle size, and the haze value is large and the product is turbid, so it has no product value. Therefore, the line roughness characteristics were not measured.
Claims
1. An anti-glare and anti-reflection plate comprising a hard coat layer, an anti-glare layer, and an anti-reflection film laminated in this order on a transparent resin substrate, the anti-glare layer being made of a cured product of a composition containing 0.1 to 15.0 parts by mass of inorganic particles having an average particle diameter (D50) of 500 nm to 700 nm per 100 parts by mass of a polymerizable acrylate compound, and the surface of the anti-glare and anti-reflection plate has the following line roughness characteristic defined in JIS B 0601: Arithmetic mean roughness (Ra) is 0.03 μm or more and 0.20 μm or less. The average length (RSm) is 10 μm or more and 70 μm or less. Skewness (Rsk) is between -0.05 and 1.
50. Kurtosis (Rku) is 2.0 or more and 5.0 or less. Maximum peak height (Rp) / maximum valley depth (Rv) is 1.0 or more and 3.0 or less An antiglare antireflection plate comprising:
2. The anti-glare anti-reflection plate according to claim 1, characterized in that the anti-reflection film is composed of a low refractive index layer having a refractive index of 1.20 to 1.45 and a layer thickness of 50 to 200 nm, the inorganic particles are silica particles, and the haze value of the anti-glare anti-reflection plate is 0.5 to 20.0%.
3. 2. The anti-glare anti-reflection plate according to claim 1, wherein the anti-reflection film comprises a medium refractive index layer having a refractive index of 1.50 to 1.75 and a layer thickness of 50 to 200 nm, a high refractive index layer having a refractive index of 1.60 to 2.00 and a layer thickness of 50 to 200 nm, and a low refractive index layer having a refractive index of 1.20 to 1.45 and a layer thickness of 50 to 200 nm, in this order, the refractive index of the high refractive index layer is higher than that of the medium refractive index layer, the inorganic particles are silica particles, and the haze value of the anti-glare anti-reflection plate is 0.5 to 15.0%.
4. The antiglare antireflection plate according to claim 1, characterized in that the antiglare layer is made of a cured product of a composition containing 100 parts by mass of a polymerizable acrylate compound consisting of 70 to 90% by mass of a hexafunctional urethane (meth)acrylate compound and 30 to 10% by mass of a di- to tetrafunctional (meth)acrylate compound (total 100% by mass), 0.1 to 15.0 parts by mass of inorganic particles, 0.1 to 1.0 part by mass of a metal chelate compound, and 0.0 to 45.0 parts by mass of silica fine particles.
5. 2. The antiglare and antireflection plate according to claim 1, wherein the antiglare layer has an average thickness of 100 to 500 nm.
6. 2. The antiglare antireflection plate according to claim 1, further comprising a protective layer and an antifouling layer laminated in this order above the antireflection film (on the viewing side).
Citation Information
Patent Citations
Antidazzle film and its manufacturing method, antireflection film, polarizing plate and image display device
JP2004333936A
Transparent substrate having antiglare properties and antireflection properties and method for producing the same
JP2018077279A